Two cases of granulomatous mycosis fungoides mimicking interstitial granulomatous dermatosis. (26th June 2022) - Stagg, Brendan; Ma, Joyce; Ibbetson, Jan; James, Craig; Ly, Hoang; Sidhu, Shireen
Abstract: Two patients presented with erythematous papules within larger patches and thin plaques. Following biopsies, each case was initially thought to represent interstitial granulomatous dermatitis (IGD); however, clinicopathological correlation led to a diagnosis of granulomatous mycosis fungoides (GMF). Drawing upon the similarities between these cases, this report explores the clinical and histological manifestations of GMF, features distinguishing GMF from other granulomatous diseases like IGD and the prognostic significance of distinguishing GMF from classic mycosis fungoides. This report also shows that despite the potential for histological overlap between GMF and IGD, the existing literature does not reveal an epidemiological or pathophysiological link between these two conditions.